2011
DOI: 10.1111/j.1528-1167.2011.03263.x
|View full text |Cite
|
Sign up to set email alerts
|

Ictal high-frequency oscillations at 80-200 Hz coupled with delta phase in epileptic spasms

Abstract: Summary Previous studies of epileptic spasms reported that ictal events were associated with high-frequency oscillations (HFOs) or delta waves involving widespread regions. We determined whether ictal HFOs at 80–200 Hz were coupled with a phase of slow-wave, whether ictal slow-waves were diffusely or locally synchronous signals, and whether the mode of coupling between HFOs and slow-wave phases differed between ictal and interictal states. We studied 11 children who underwent extraoperative electrocorticograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 12 publications
6
74
1
Order By: Relevance
“…The neurobiological basis for these brief seizures is unknown but results from clinical studies have implicated a possible interaction between abnormal neocortical and subcortical circuits in their generation (Chugani et al , 1992, Dulac et al , 2002, Lado and Moshe, 2002, Hrachovy and Frost, 2003). A neocortical contribution of abnormal HFOs to spasm generation is supported by recent recordings in both humans and animals (Frost et al , 2011, Nariai et al , 2011a, Nariai et al , 2011b, Frost et al , 2012). …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The neurobiological basis for these brief seizures is unknown but results from clinical studies have implicated a possible interaction between abnormal neocortical and subcortical circuits in their generation (Chugani et al , 1992, Dulac et al , 2002, Lado and Moshe, 2002, Hrachovy and Frost, 2003). A neocortical contribution of abnormal HFOs to spasm generation is supported by recent recordings in both humans and animals (Frost et al , 2011, Nariai et al , 2011a, Nariai et al , 2011b, Frost et al , 2012). …”
Section: Introductionmentioning
confidence: 75%
“…Neurophysiological studies of epileptic spasms in humans and an animal model have reported the presence of abnormal HFOs in EEG recordings (Panzica et al , 2007, Frost et al , 2011, Nariai et al , 2011a, Nariai et al , 2011b, Frost et al , 2012). Infantile spasms is the most common form of epileptic spasms.…”
Section: Introductionmentioning
confidence: 99%
“…There are increasing numbers of studies pointing to the importance of high frequency activity - HFA (Jiruska and Bragin, 2011; Jiruska et al, 2010; Jouny et al, 2007b; Rodin et al, 2009), or high frequency oscillations (HFOs) (Burns et al, 2012; Firpi et al, 2007; Jacobs et al, 2008; Jacobs et al, 2010; Jirsch et al, 2006; Nariai et al, 2011a; Ochi et al, 2007; Rampp and Stefan, 2006; Worrell et al, 2008; Worrell et al, 2004), for localizing the seizure onset zone. Recent studies have reported increased postsurgical seizure-free outcomes after resection of brain regions revealing ictal HFOs (Fujiwara et al, 2012; Jacobs et al, 2012; Jacobs et al, 2010; Modur et al, 2011; Nariai et al, 2011b; Ochi et al, 2007; Zijlmans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cotic and colleagues have previously shown that epileptic regions that demonstrate local cross-frequency interactions are also areas of increased interelectrode coherence (Cotic et al 2011), and Nariai and colleagues have demonstrated a tight coupling between the phase of slow waves (defined as Յ1 Hz in their study) during epileptic spasms and ictal pHFOs (Ͼ80 Hz) (Nariai et al 2011). Our present finding of elevated interregional slow frequency connectivity within the SOZ during seizure initiation and propagation adds additional emphasis on the role of slow oscillations during seizures.…”
Section: Discussionmentioning
confidence: 99%